APOLOGIA CORRUPTION VS PUNITIVE RESPONSES: A CONTENT ANALYSIS AND AN EXPERIMENTAL STUDY ON APOLOGIA STRATEGY OF THE SUSPECTED CORRUPTORS AND THE PUBLIC RESPONSES - Kriyantono R. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
Apologia and Attribution theories are used to explain whether the apologia strategies of the suspected corruption affect the public’s punitive responses in crisis situation. Attribution theory suggests that every individual or institution may be criticized for their actions and suggests the possible consequences of attribution on punitive responses. Apologia theory suggests anticipative strategies for possible accusations to gain positive attribution. This research applies a content analysis on 50 news containing the apologia strategies of the corruption actors published in online media and an experiment on 100 participants to measure whether the strategies influencing the public’s punitive responses. The findings indicate that both actors, the caught and the suspects, use predominantly bolstering strategies. Bolstering strategy results in much higher sympathy for both actors and reduces the public’s punitive responses against the actors although it is not likely to completely remove the public anger.